Antiplatelet therapy in the primary prevention of cardiovascular disease in patients with chronic obstructive pulmonary disease: a randomised controlled proof-of-concept trial. Issue 3 (5th August 2019) - Kunadian, Vijay; Wilson, Nina; Stocken, Deborah D.; Ali, Hani; McColl, Elaine; Burns, Graham; Howe, Nicola; Fisher, Andrew; De Soyza, Anthony
The APPLE COPD-ICON2 trial is a prospective 2×2 factorial, double-blinded proof-of-concept randomised controlled trial targeting patients with chronic obstructive pulmonary disease (COPD) without prior history of cardiovascular disease. The primary goal of this trial is to investigate if treatment with antiplatelet therapy will produce the predefined cut-off of platelet inhibition measured using the Multiplate test in COPD patients. Eligible patients were randomised to aspirin plus placebo, ticagrelor plus placebo, aspirin plus ticagrelor or placebo only for 6 months. The primary outcome comprises inhibition (binary response) of arachidonic acid- (ASPI test, cut-off <40) and adenosine diphosphate- (ADP test, cut-off <46) induced platelet aggregation at 6 months. 543 patients were screened and 120 patients were recruited with mean age of 67.5 years; 47.5% patients were male. The per-protocol ASPI test response rate to aspirin was 68.3% (95% CI 52.3–80.9%). The per-protocol ADP test response rate to ticagrelaor was 68.8% (95% CI 50.4–82.6%). Platelet response to antiplatelet therapy with aspirin and ticagrelor was not observed in nearly one-third of COPD patients without prior history of cardiovascular disease. These findings support the high pro-thrombotic milieu and the need for further research to determine the effect of antiplatelet/antithrombotic therapy on cardiovascular morbidity and mortality in COPD patients. COPD is the world's number 2 killer. In our study, treatment with antiplatelet therapy in COPD patients did not lead to adequate platelet response in just under a third of patients, emphasising the high thrombotic milieu in these patients. http://bit.ly/2WT8241